IMPROVED CATALYTIC ACTIVITY OF ASPERGILLUS ORYZAE 2-GALACTOSIDASE BY COVALENT IMMOBILIZATION ON EUPERGIT CM - Y. Aslan; A. Y. Taher; . Cavidolu (Journal of Animal and Plant Sciences, 2018)
In this study, Aspergillus oryzae 2-Galactosidase ( AOG) was immobilized onto Eupergit CM. By optimizing the immobilization conditions such as pH and molarity of immobilization buffer, enzyme/support ratio and duration of immobilization, 100.00% immobilization yield and 129.82% activity yield was achieved. The optimum temperature ( 55 °C) of free enzyme was not changed while optimum pH of free enzyme was shifted from 4.5 to 5.5 after immobilization. Kinetic constants for free and immobilized enzyme were also determined by using the Lineweaver-Burk plot. The K m values of the free and immobilized enzymes were determined to be 307.7 and 234.2 g / L respectively, while the V max values were determined to be 0.366 g D-Glucose / L.min and 0.415 g D-Glucose / L.min respectively. The operational and storage stabilities of immobilized enzyme were also studied. The activity of immobilized enzyme decreased to 99.3% after repeated twenty usage while decreased to 98.3% after fifteen days of storage. Further, the immobilized enzyme was used for the hydrolyzing the cow's milk lactose. By using the immobilized enzyme, the milk lactose was completely hydrolyzed in four hours. Consequently, immobilized AOG can be used in the industrial production of lactose-free cow's milk. lactose intolerance continuous production processes in the industry. Thus
Keywords: Aspergillus oryzae; 2-Galactosidase; covalent immobilization; Eupergit CM; lactose-free cow's milk